INVESTIGATION INTO A MEMS BASED 3-AXIS MAGNETIC SENSOR UTILIZING LORENTZ FORCE - MIAN, MUHAMMAD UMER (2018)
This thesis presents a study on a Micro Electro Mechanical Systems (MEMS) based 3-axis magnetic sensor for applications requiring low magnetic field detection (1 T – 100 mT). Simultaneous measurements of 3-axis magnetic fields are required for compass applications.